1993
DOI: 10.1182/blood.v82.4.1328.1328
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of erythrocytes in a strong static magnetic field

Abstract: The frequency of exposure to strong magnetic fields has increased as the magnetic-resonance image-diagnostic technique (MRI) and passenger transport systems based on the principle of magnetic levitation have come into wider use. Accordingly, it has become necessary to more systematically assess their influence on the body and set strict guidelines on acceptable limits of magnetism exposure. Therefore, we have assessed the influence of an uniform static magnetic field (8 T in maximum) on normal erythrocytes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(41 citation statements)
references
References 23 publications
2
39
0
Order By: Relevance
“…The MC3T3-E1 cells, which adhered to the culture dish, were magnetically orientated because of their diamagnetic anisotropy. The possible origins of diamagnetic anisotropy of cells are reportedly the cell membranes and intracellular cytoskeleton molecules in erythrocytes (13)(14)(15) and platelets. (16) Because the diamagnetic anisotropy is canceled in spherical or symmetrical shapes cells, the irregular and asymmetrical shapes seen in erythrocytes, platelets, and osteoblasts will result in the large diamagnetic anisotropy of these cells.…”
Section: Static Magnetic Field On Bone Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The MC3T3-E1 cells, which adhered to the culture dish, were magnetically orientated because of their diamagnetic anisotropy. The possible origins of diamagnetic anisotropy of cells are reportedly the cell membranes and intracellular cytoskeleton molecules in erythrocytes (13)(14)(15) and platelets. (16) Because the diamagnetic anisotropy is canceled in spherical or symmetrical shapes cells, the irregular and asymmetrical shapes seen in erythrocytes, platelets, and osteoblasts will result in the large diamagnetic anisotropy of these cells.…”
Section: Static Magnetic Field On Bone Formationmentioning
confidence: 99%
“…The minimum period of magnetic field exposure for attaining the parallel orientation of MC3T3-E1 cells was 60 h in this study, whereas in floating cells such as erythrocytes and platelets, the regulation of orientation was observed within 1 minute. (13)(14)(15) This difference may be caused by the presence and absence of friction between cells and the culture dish surface, which may prevent the movement of adherent cells. It appears that the magnetic orientation of cells occurs when the diamagnetic torque force overcomes the force of friction.…”
Section: Static Magnetic Field On Bone Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…1984; Kotani et al, 2000] and fibrin aligns parallel [Torbet et al, 1981;Ueno et al, 1993] to the magnetic field when exposed to strong magnetic fields during polymerization. Floating cells such as erythrocytes [Higashi et al, 1993] and adherent cells such as osteoblasts [Kotani et al, 2000[Kotani et al, , 2002 also orientate parallel to the direction of the magnetic field. We previously reported that Schwann cells aligned along collagen fibers oriented by an 8-T magnetic field [Eguchi et al, 2003;Eguchi and Ueno, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these nerve conduits have achieved therapeutic effects comparable to autografts. Recently, many studies have reported that strong magnetic fields of tesla (T)-order could orient an extracellular matrix such as collagen [Torbet and Ronziere, 1984;Kotani et al, 2000] or fibrin [Torbet et al, 1981;Ueno et al, 1993], floating cells such as erythrocytes [Higashi et al, 1993], and adherent cells such as osteoblasts [Kotani et al, 2000[Kotani et al, , 2002. This ability to control orientation of biological materials may be useful in medical and tissue engineering.…”
Section: Introductionmentioning
confidence: 99%